Economic Evaluation of the Portuguese Needle Exchange Program in Community Pharmacies (NEP-CP) - M Gouveia; AV Carneiro; S Costa; J Guerreiro; M Cary; G Jesus; M Gouveia; M Borges (Formifarma, LDA., 2019)
Objectives To conduct a cost-effectiveness analysis comparing two scenarios of the Needle Exchange Program (NEP) in Portugal: with and without community pharmacies (CP). Methods Health gains were measured by the number of HIV and HCV infections avoided. The number of infections in each scenario was estimated based on a standard model in the literature (Jacobs et al, 1994) calibrated to the national epidemiological situation taking into account the trend of infections' incidence and the characteristics of Injecting Drug Users (IDU). The costs per averted infection were taken from the national literature. The estimates of the NEP-CP costs include costs incurred by CP and by other institutions that participate in the logistics of the manufacturing, distribution collection and incineration of injection materials. The results were presented as net-costs, i.e., the monetary value of infections avoided less the incremental costs of the NEP-CP. Results Using a 5-Year Time Horizon, it was estimated that the NEP-CP would account for a 6.8% reduction of (n=25) of HCV infections and 6.5% reduction of (n=22) HIV infections among IDU. Over this time horizon, the current value of annual net savings generated by the participation of the community pharmacies in the NEP was estimated at €2,073,347. Over the five years, each syringe exchanged has an average discounted net-benefit of €3.01. Conclusions The participation of community pharmacies in the NEP leads to a reduction of HIV and HCV infections and generates savings for the health system of more than two million euros. The NEP-CP is dominant over the alternative scenario, i.e., generates better health outcomes at a lower cost, contributing significantly to improve the efficiency of the public health system in Portugal.  Published in: ISPOR 19th Annual European Congress, November 2016, Vienna, Austria.